Synthesis and thermodynamic characterization of poly(methyl methacrylate)/multiwall carbon nanotube nanocomposite - Cakar, Fatih (WILEY, 2021)
In the first part of this study, poly(methyl methacrylate) (PMMA)/multiwall carbon nanotube (MWCNT) nanocomposite was synthesized by adding carbon nanotube before polymerization with bulk polymerization. Surface morphology of the PMMA/MWCNT nanocomposite and the PMMA/MWCNT nanocomposite with Chromosorb W was characterized by scanning electron microscopy (SEM). Surface and thermodynamic properties of the PMMA/MWCNT nanocomposite were investigated by inverse gas chromatography (IGC). The surface acid base character and dispersed surface energy gamma SD of the PMMA/MWCNT were determined at infinite dilution. The entropy of adsorption, increment S-S, the specific free energy of adsorption, increment G(S), and the enthalpy of adsorption, increment H-S, of selected polar solvents were determined on the PMMA/MWCNT nanocomposite. The values of increment H-S were correlated with both the acceptor and donor numbers of the solvents to determine the Lewis acidic constant K-A and the Lewis basic constant K-D of the PMMA/MWCNT nanocomposite. The PMMA/MWCNT nanocomposite selectivity was investigated using the acetate and alcohol isomers by IGC at temperatures between 393.2 and 403.2 K. Glass transition temperature (T-g) was determined using differential scanning calorimetry (DSC) and IGC method. The interactions between the PMMA/MWCNT nanocomposite and 12 solvents were propped at a temperature range (423.2-448.2 K). The Flory-Huggins interaction parameter, chi 12 infinity, and the weight fraction activity coefficient, omega 1 infinity, of the PMMA/MWCNT nanocomposite solvent system were estimated at temperatures between 423.2 and 448.2 K. The solubility parameter of the PMMA/MWCNT nanocomposite, delta(2), was calculated as 14.0 (cal/cm(3))(1/2).
Keywords: acid– base interactions; inverse gas chromatography; isomer selectivity; multiwall carbon nanotube; poly(methyl methacrylate); solubility parameter; surface energy; INVERSE GAS-CHROMATOGRAPHY; POLY ETHER IMIDE; PHYSICOCHEMICAL PROPERTIES; SURFACE CHARACTERIZATION; ADSORPTION; SOLUBILITY; SOLVENTS; OXIDE; TRANSITION; PARAMETERS; Chemistry